The Effect of Two Kinds of Aerobic Exercise on the Static and Dynamic Balance of Old Men - Mojtaba Kashefi; Rasoul Hemayat talab; Morteza Pour Azar; Mojtaba Dehestani Ardakani (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: The aim of present study is to determine the effect of two methods of aerobic training on static and dynamic balance in old men.  Methods & Materials: 37 aged people over 60 years old who were physically healthy divided into three groups after randomly carrying out pretest: 1) walking or running aerobic exercise group (n=12), 2) cycling aerobic exercise group (n=13) and 3) control group (n=12). Then groups 1 and 2, participated in running or walking exercise and cycling aerobic exercise as well with 60 percent of maximum heartbeat intensity. These two groups who were considered experimental groups of research appeared on exam site for 8 weeks, each week 3 sessions and each session 45 minutes. They rested one day between every two sessions of exercise. During the project group 3 (control) continued its daily activities and had no especial exercise. After the training period, all subjects participated in the posttest session. In order to measure the static and dynamic balance Sharpend Romberg test and balancing timber test were used. The covariance analysis test (ANCOVA) was also applied to examine the effect of exercise on the dependent variables and to study differences between group.  Results: The findings showed that exercise training programs in both experimental groups in research compared with control group significantly improved static and dynamic balance of subjects. It was also showed that the development of the first group (walking or running exercise group) in both static and dynamic balance test was significantly higher than Group 2 (bike exercise group).  Conclusion: According to the results, it is recommended that trainers, organizations and institutions that deal with the elderly, use the cycling and walking exercises, especially walking and jogging to reduce the risk of further problem in these people.